Risk Factors for Early Hydrocephalus on Post Unilateral Thalamic Tumor Resection - Zhang, Linpeng; Wang, Chen; Zeng, Xianwei (Frontiers in surgery, 2022)
The outcome of surgical treatment for thalamic tumors is poor. Hydrocephalus is one of the most frequent postoperative complications after unilateral thalamic tumor resection. This study examined the relationship between surgical approaches, pathological grade, image characteristics, preoperative complications, extent of resection, and incidence of postoperative hydrocephalus. The study retrospectively reviewed clinical data from 80 patients who underwent resection of thalamic tumors between 2015 and 2021. Data on patient survival and disease progression status were obtained retrospectively to calculate overall survival (OS) and progression free survival (PFS). No patients died during the perioperative period and two patients suffered postoperative coma. Tumors were totally resected in 44 cases (55 %), subtotally resected in 21 cases (26.25 %), and partially resected in 15 cases (18.75 %). Thirty-five cases of hydrocephalus occurred within 1 month after operation(43.75%). Surgical approaches associated with hydrocephalus were as follows: hydrocephalus occurred in seven cases after trans-frontal lateral ventricle approach for tumor resection (62.9%), in 17 cases after through parieto-occipital transventricular approach tumor resection (43.58%), and in one case after trans-frontal lateral ventricle approach for tumor resection + third ventriculostomy (7.1%). Postoperative muscle strength decrease occurred in 41 patients (51.25%). Longer PFS and OS were correlated with degree of resection in patients with thalamic glioblastoma ( < 0.05) and had no relationship with hydrocephalus. Surgical treatment of thalamic tumors is an effective therapeutic method. The incidence of postoperative hydrocephalus is not associated with tumor size, degree of tumor enhancement, peritumoral edema, tumor invasion, midline crossing, and pathological grade. The incidence of postoperative hydrocephalus was higher in patients with preoperative hydrocephalus and low resection degree, and lower in patients with endoscopic third ventriculostomy. The risk of early postoperative hydrocephalus in thalamic tumors is high. Intraoperative third ventriculostomy could reduce the incidence of early postoperative hydrocephalus. PFS and OS were longer in patients with thalamic glioblastoma with a high resection degree ( < 0.05) and were not associated with hydrocephalus.